13: MOVEMENTS, BEHAVIOR, AND NESTING ECOLOGY OF THE WILD TURKEY IN EASTERN ALABAMA* - Hilburn O. Hillestad (Wildlife Society Bulletin)
ABSTRACT An ecological study of the eastern wild turkey (Meleagris gallopavo silvestris) was conducted in the Alabama Piedmont during the spring and summer of 1968 and 1969. Fifteen hens were captured, patagium‐tagged, instrumented with 27 MHz radio transmitters, and released at the capture sites. Twelve hens provided significant data on movements, behavior, and nesting. Spring and summer ranges of four nonnesting hens averaged 194 acres; spring and summer ranges of eight nesting hens averaged 370 acres. Movements to nest sites from capture sites averaged 0.8 mile; maximum straight‐line movement for eight nesting hens averaged 1.7 miles. Predators caused five nest failures; three nests were successful. There was no renesting. Seven hens selected similar nesting habitat but were separated by distances up to 5 miles. Their selected nest sites were in open, recently cut‐over upland pine habitat. Both sociological and ecological factors were believed to have influenced five hens that nested in close proximity. Adult hens were believed to initiate the dispersal of juvenile gobblers from the family flock. Juvenile gobblers dominated juvenile hens, but were subordinate to adult hens in family flocks. Survival of poults is possibly aided by this hierarchic arrangement. Additional behavior of nonnesting hens and of nesting hens is reported.